Correlation Between Islamic Religiosity and Mental Well-Being in Students in the Perspective of Achieving Sustainable Development Goals (SDGs) - Pauline Hapsari; Darodjat (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to analyze the correlation between Islamic religiosity and mental well-being among college students and to identify the potential of religiosity in predicting mental well-being. This research contributes to the achievement of the Sustainable Development Goals (SDGs), particularly Goal 3 on good health and well-being, by providing insights into the importance of religiosity in supporting mental well-being. Theoretical framework: The theoretical framework highlights the relationship between religious beliefs and mental health, where religiosity functions as an effective coping mechanism. Literature Review: Relevant literature indicates that religiosity is often associated with improved psychological well-being through stress reduction and enhanced life meaning. Methods: The study employed a correlational research design involving 32 college students as participants. The research instruments included the Islamic Religiosity Questionnaire and the Mental Well-Being Questionnaire, analyzed using SPSS software. Results: The linearity test confirmed that the data were linear, with a sig. Deviation from linearity value of 0.467 (> 0.05). The Pearson Product Moment correlation test results showed a p-value of 0.019 (< 0.05) and a correlation coefficient of 0.413, indicating a moderate positive correlation between religiosity and mental well-being. This suggests that higher levels of religiosity are associated with better mental well-being among college students. Implications: The implications of this study include recommendations for higher education institutions to integrate religious values into mental health support programs to advance the SDGs. These findings also provide a new perspective on a holistic approach to student mental health by considering spirituality as a significant predictor. Novelty: The novelty of this research lies in linking Islamic religiosity with mental well-being within the framework of SDGs, a topic rarely explored in previous studies.